A study on factor that effect foreign customer loyalty in Telekom Malaysia Berhad / Nurul Atiqah Mohamad Azahar - Mohamad Azahar, Nurul Atiqah (2011)
The purpose of the study is to determine factors that effect foreign customer loyalty which can contribute as a benchmark for the successful of the TM customer service’s quality program imposed by the company. Research work was aimed to examine the relationship between factors that effect customer’s loyalty in TELEKOM. This study helped determine whether factors that effect foreign customer’s loyalty have any impact to maintaining their customer, be it a positive or negative impact. For this paper, a survey on the impact of factors that effect foreign customer’s loyalty were conducted to measure whether or not it has trigger as a reason TELEKOM cannot maintain their foreign customer. 100 respondents were also asked to complete a questionnaire concerning their views on the factors that effect foreign customer’s loyalty consists of five sections. The results of this study shows whether there have any relationship between factors that effects foreign customer’s loyalty.